Experimental and Computational Evidence for the Mechanism of Intradiol Catechol Dioxygenation by Non-Heme Iron(III) Complexes - Jastrzebski, Robin; Quesne, Matthew G.; Weckhuysen, Bert M.; de Visser, Sam P.; Bruijnincx, Pieter C. A. (Chemistry : a European journal, 2014)
Catechol intradiol dioxygenation is a unique reaction catalyzed by iron‐dependent enzymes and non‐heme iron(III) complexes. The mechanism by which these systems activate dioxygen in this important metabolic process remains controversial. Using a combination of kinetic measurements and computational modelling of multiple iron(III) catecholato complexes, we have elucidated the catechol cleavage mechanism and show that oxygen binds the iron center by partial dissociation of the substrate from the iron complex. The iron(III) superoxide complex that is formed subsequently attacks the carbon atom of the substrate by a rate‐determining CO bond formation step. Reaction mechanism: The combination of experimental and computational work has revealed that in catechol intradiol dioxygenation, oxygen binds to iron first, facilitated by partial dissociation and one‐electron oxidation of the substrate (see scheme). The subsequent attack of oxygen on the substrate carbon atom was shown to be the rate‐determining step in this unique reaction.